Application of metabolomics and network analysis to reveal the ameliorating effect of four typical "hot" property herbs on hypothyroidism rats - Yang-Yang Wang; Yan-Ping Sun; Bing-You Yang; Qiu-Hong Wang; Hai-Xue Kuang (Frontiers Media S.A., 2022)
Herbs with a "hot" properties are frequently used to treat cold symptoms in TCM. However, the underlying mechanisms of the herbs with "hot" properties on hypothyroidism have not been investigated. This study aimed to explore four typical "hot" and "cold" property herb on hypothyroidism. Firstly, the difference efficacy between the four typical "hot" property herbs and the four typical "cold" property herbs was assessed by physical signs, thyroid function, and the metabolic profile using multivariate statistical analysis. The influence of the four typical "hot" property herbs on hypothyroidism was validated pathologically. The impact mechanism of the four typical "hot" property herbs on hypothyroidism was investigated through a metabolomics method combined with network analysis. Na+/K+-ATP, ACC1 enzyme, UCP-1, and the PI3K-Akt pathway were used to confirm the metabolite pathways and target-associated metabolites. The results showed that the four typical "hot" property herbs could significantly improve physical signs, thyroid function, and the metabolic profile in hypothyroidism rats, the four typical "cold" property herbs did not show any benefit. Moreover, the four typical "hot" property herbs could improve lipid metabolism, energy metabolism, and thyroid hormone levels by the PI3K-Akt signaling pathway, Ca2+- AMPK signaling pathways, purine metabolism, and tryptophan metabolism. Additionally, the levels of UCP-1, Na+/K + -ATP enzyme, and ACC1 were ameliorated by the four typical "hot" property herbs in hypothyroidism rats. Therefore, a metabolomics strategy combined with network analysis was successfully performed and interpreted the mechanism of the four typical "hot" property herbs on hypothyroidism based on the theory of "cold and hot" properties of TCM well.